Gendered Social Policies in (Post-)Communist Countries: The Case of Poland - Zok, Michael (Ревија за социјална политика/Journal of Social Policy, 2022)
The conservative “backlash” of the 1980s did not only apply to women’s rights but also to social policies. It was often perceived as a phenomenon of the so-called “first world”. However, current historical research on state-socialist countries shows that it could also be observed in these particular countries, for example in social policies in communist Poland. There, a new government under the leadership of Edward Gierek came into power in 1970 and tried, on the one hand, to modernize the economy in an effort to improve its international competitiveness. On the other hand, the new leadership also tried to build a “second Poland” by raising the standard of living. Social policies became an important tool to ensure communist preservation of power at that time. However, this, in the end failed, attempt to modernize Poland led to a (re-)traditionalization of family life and gender relations. Ultimately, this meant that the government tried to remove women from the labour market. This was closely connected to a discourse on a “crisis of demography” that became prominent during the 1970s and influenced subsequent governments regarding their social policies. The article analyses these developments in social policies in Communist Poland and situates them in a wider context by looking at the first years of transformation in the 1990s. It will therefore highlight continuities and fractions in this particular political field between late and post-communism.